DNA barcoding and faunistic criteria for a revised taxonomy of Italian Ephemeroptera. Issue 1 (1st January 2018) - Tenchini, R.; Cardoni, S.; Piredda, R.; Simeone, M. C.; Belfiore, C.
Abstract: Mayfly (Ephemeroptera) systematics has considerably changed over the years, but many questions have yet to be answered. The synergistic connection between traditional knowledge and new data sources, producing increasingly complex information, has become a compelling issue for modern taxonomy. Molecular tests and the use of reliable reference sequence libraries may constitute effective complements to the traditional method in guiding recognition of species and giving information about taxonomic incongruences which require further examination. In the present study, we sought to verify the current Italian mayfly nomenclatural system through DNA barcoding and relevant points to reliably manage the available amount of morpho-ecological and molecular data are discussed. We investigated COI (Cytochrome oxidase I) sequence variation in 163 individuals of Italian mayflies, 126 of which were previously assigned to 24 morphologically recognised species, and 37 could be attributed only to generic taxonomic entities ("sp.", "cf." or "gr."). DNA barcoding statistical tests for species delimitation hypotheses based on genetic distances and inferred gene trees were integrated with GenBank searches and surveys of the historical literature to better understand the knowledge acquired on the status and diversity of the investigated taxa. Combined criteria to define three categories of reliability were then assessed. Concurrent data allowing unambiguous identification were attained for only eight species. High intraspecific genetic distances (> 3%) and a lack of reliable reference material or convincing taxonomic information evidenced 29 critical states, deserving further investigation. Solid species names, potential cryptic species and entities about which little is known are pointed out for a future upgrade/reorganisation of the taxonomy of Italian Ephemeroptera.